Precision Health in Disaster Medicine and Global Public Health. Issue 6 (20th December 2018) - Patel, Ronak B.
Abstract: Current debates about precision medicine take different perspectives on its relevance and value in global health. The term has not yet been applied to disaster medicine or humanitarian health, but it may hold significant value. An interpretation of the term for global public health and disaster medicine is presented here for application to vulnerable populations. Embracing the term may drive more efficient use and targeting of limited resources while encouraging innovation and adopting the new approaches advocated in current humanitarian discourse. RB. Patel Precision health in disaster medicine and global public health .Prehosp Disaster Med .2018 ;33 (6 ):565 –566 .